The reliability of using a laser device to assess deceleration ability - Ashton, J.; Jones, P. A. (Sports, 2019)
An important component of change of direction speed is the ability to decelerate. Objective methods to examine this quality have been rarely reported in the literature. The aim of this study was to investigate the within- and between-session reliability (intraclass correlation coefficients (ICC), coefficient of variation (CV), standard error of measurement (SEM) and smallest detectable difference (SDD)) of using a laser Doppler device (LAVEG—LAser VElocity Guard) to quantify deceleration ability in 20 amateur rugby union players. Each player performed one familiarisation and two experimental sessions (seven days apart) consisting of three maximal 15 m sprints from a standing start, with an immediate deceleration to a complete stop upon hearing an audible cue at the 15 m mark. Deceleration was evaluated by determining the distance required to decelerate to 75%, 50%, 25% and 0% (`stopping distance`) of the velocity achieved at 15 m of the maximal sprint. Within-session relative reliability was moderate to good (ICC = 0.64-0.83) with borderline acceptable variation (CVs = 10.51%-16.71%) across all variables. Between-session reliability reported good to excellent relative reliability (ICC = 0.79-0.93) with acceptable absolute reliability, particularly for stopping distance (SEM: 6.54%; SDD: 9.11%). The assessment shows promise as a method to quantify deceleration ability in athletes